Design and Simulation of Dual-Band Nonuniform Relativistic Backward Wave Oscillator Using a Bragg Structure as Its RF Circuit and Reflector-Cum-Mode Converter - Ansari M.A.; Thottappan M. (My University, 2025)
A relativistic backward wave oscillator (RBWO) operating in dual ( C and X ) band is designed and studied using finite-difference time domain (FDTD) particle-in-cell (PIC) simulations implemented in MAGIC. It consists of a sinusoidally corrugated, moderately overmoded nonuniform slow wave structure (SWS) in the downstream section and a single fold two-way helically corrugated Bragg structure in the upstream section. A single intense relativistic electron beam (IREB) having 5.1 kA of current is predicted for 600 kV of diode voltage. An RF output power 720 MW in X -band and 510 MW in C -band are predicted in TE11 mode with a guiding magnetic field of 2.5 T. © 1963-2012 IEEE.